Affective polarization and coalition preferences in times of pandemic - Bettarelli, Luca; Van Haute, Emilie (Frontiers in Political Science, 2022)
Using the RepResent Voter Panel Survey conducted in Belgium since the 2019 Federal elections, we investigate the relationship between affective polarization and voters' coalition preferences, in the first phase of the COVID-19 pandemic. Results confirm a strict negative link between affective polarization and preferences for coalitions in general. Such result is robust to different types of coalitions, in terms of number and size of parties, as well as the ideological position of voters. However, we also show how the negative effect of affective polarization can be moderated if the coalition includes the voter's in-party. Overall, our results help better understanding the political consequences of affective polarization in a multiparty setting.